Informing policy with agricultural R&D evidence: An ASTI pilot project in Ethiopia, Nigeria, and Tanzania - Carden, Fred; Beintema, Nienke M.; Admassie, Assefa; Katera, Lucas; Mboghoina, Thadeus; Onyekwena, Chukwuka (International Food Policy Research Institute, 2019)
Despite Agricultural Science and Technology Indicators’ (ASTI) global and regional visibility-and the use of its data for institutional decision-making by various national agricultural research institutes-the incorporation of ASTI evidence into national policymaking remains mostly ad hoc and is often indirect. Moreover, interventions to influence the uptake of ASTI data for this purpose have been limited. Given agricultural research’s important role in increasing agricultural productivity, economic growth, and poverty reduction, ASTI initiated a pilot study in three African countries (Ethiopia, Nigeria, and Tanzania) to develop a clearer understanding of how to promote the uptake of agricultural research evidence. The study focused on how evidence in general, and ASTI evidence in particular, could be more effectively integrated at the national level, particularly to promote the allocation of sustainable resources to agricultural research. The study was conducted in two stages: (1) the mapping of each country’s agricultural research interests and issues; and (2) identifying initial activities through which those interests offered opportunities both to fill research gaps and enhance the utility of agricultural research. Findings from the pilot studies point to opportunities for improving the availability, accessibility, appropriateness, and ownership of ASTI evidence to ensure that it contributes more effectively as a valuable resource for decision-making. Strong relationships and networks are needed to increase awareness of ASTI evidence and to institute linkages with official national data systems. Outcomes indicated both interest in the evidence and recognition of its merit. Greater outreach and connectivity with local institutions may be useful next steps. These findings lead to some general recommendations for improving the use of evidence, along with specific recommendations for the ASTI network approach moving forward. Shifting ownership of the data and systems to the regional and national levels-a key objective of the network approach-is a long-term undertaking. A transition period is needed, accompanied by a strategic plan to shift responsibility and action, first to the regional level and then to the national level where feasible.